1969-1977. The construction of the image of the Spanish monarchy through opinion polls - Magallón Rosa, Raúl (Hispania Nova, 2021)
The aim of this study is to analyze the role of censored and silenced polls in the Spanish. This paper analyzes the opinión polls never made public by Foessa and the the Spanish Institute of Public Opinion - renamed CIS in 1977 –, in addition to the opinion studies carried out since 1976 by Gallup Spain. What the different polls showed was that not even a dictatorship that had lasted 30 years had achieved the social and cultural consensus needed to make social and legal legitimation match.